THE IMPACT OF INTEGRATED PEDAGOGICAL TECHNOLOGIES IN MEDICAL EDUCATION ON STUDENTS' LEARNING INDICATORS (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the role of pedagogical and medical approaches in teaching complex clinical subjects to medical students. The study highlights the effectiveness of interactive visualization methods and cognitive psychology principles in reinforcing student knowledge.